Experimental analysis of hardness and tensile characteristics of copper reinforced AA6061 stir cast composites subjected to thermal and deformation assisted heat treatments. Issue 1 (31st December 2023) - Sadanand, Ramakrishna Vikas; Sharma, Sathyashankara; Prabhu, P. R.
Abstract: Aluminium alloy 6061 based composites reinforced with a varied weight percentage of copper particulates are fabricated utilizing a liquid metal stir casting technique. The collective influence of copper reinforcement, age hardening and low temperature thermomechanical treatment on AA6061 was investigated. The age hardened composites displayed better hardness and ultimate tensile strength than as cast composites. Thermomechanical treatment of the composites further enhanced the mechanical properties and hence showed better results over age hardened composites. The study revealed that an increase in the deformation enhanced the hardness and strength of the composite while the aging time to achieve the peak hardness was reduced. Both age hardened and thermomechanically treated composites with 6 wt.% copper reinforcement indicated the best peak hardness and UTS values at the lower aging temperature of 100 °C. The thermomechanically treated composite with 6 wt.% Cu, 15% deformation aged at 100 °C showed 80 and 69% increase in hardness and UTS, respectively, over as cast composite. Fracture surface analysis of the as cast, age hardened, and thermomechanical treated composites showed a mixed mode of fracture dominant with the brittle failure.